Keeping the safety messages simple: the international task force on open-water recreational Drowning Prevention - Quan, L.; Bennett, E.; Moran, K. (Biomechanics and Medicine in Swimming XI, 2010)
Globally, many organizations addressed the risk of drowning associated with aquatic recreation by promoting a plethora of drowning prevention messages. Preliminary discussion among drowning prevention advocates suggested that messages could be contained within simplified generic messages applicable to all settings. Using a modified Delphi technique to harness expert opinion, the Task Force finally agreed on 16 key messages that would foster open water drowning prevention. Messages were categorized into Care of self and on the Care of others. Learning swimming and water safety survival skills was the dominant message in both categories. It is hoped that by providing simple and consistent prioritised safety messages that are applicable to a range of communities and settings, the ultimate goal of saving lives will be achieved.